ANALISIS PERAN PENDIDIKAN MULTIKULTURAL DALAM UPAYA MENINGKATKAN SIKAP TOLERANSI SISWA DI SEKOLAH INKLUSI - Nadya Safitri, Salsa; Zakiah, Linda; Wahyuningsih, Sri; Dini Hayati, Syifa; Ashri Maulidina, Citra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Multicultural education has become an important focus in efforts to create an inclusive educational environment and attitudes of tolerance in inclusive schools. This article aims to investigate and explain the important role of multicultural education in efforts to increase students' attitudes of tolerance in inclusive schools. Through a comprehensive literature review, this article aims to identify multicultural education strategies and practices that are effective in forming attitudes of tolerance among students who have diverse cultural, religious and social backgrounds. This research was conducted using qualitative research, literature study or research literature. The data taken comes from research that already exists on the internet. The results of the research show that multicultural education plays an important role in increasing students' tolerant attitudes in inclusive schools. The conclusion is that multicultural education has an important role in students' tolerant attitudes in inclusive schools.